Learning that comes from the negative interpretation of life experiences - Sharan Merriam; Vivian Mott; Ming-yeh Lee (Adult Education Research Conference, 1996)
The prevailing assumption underlying much of the adult learning literature is that growth-oriented changes are the result of adult learning. The purpose of this qualitative study was to understand the process involved when the learning from the negative interpretation of a life experience results in growth-inhibiting, rather than growth-oriented outcomes. Data analyzed from 18 participants revealed that if a life experience challenges some central defining aspect of the self, and the challenge is perceived as too threatening to the self, growth-inhibiting responses, including blame, hostility, withdrawal, and distrust are learned in order to protect self. However, when and if the threat to the self is reduced, the process may reverse itself toward more growth-oriented outcomes.